Molecular epidemiology of Streptococcus pneumoniae isolated from pediatric community-acquired pneumonia in pre-conjugate vaccine era in Western China - Zhuoxin Liang; Jinjian Fu; Ling Li; Rongsong Yi; Shaolin Xu; Jichang Chen; Xiaohua Ye; Eric McGrath (BMC, 2021)
Abstract Background Streptococcus pneumoniae (S. pneumoniae) is one of the most common pathogens which can cause morbidity and mortality in pediatric infections worldwide. This study aimed to describe the phenotypic and molecular characteristics of community-acquired pneumonia (CAP)-causing S. pneumoniae recovered from children in Western China. Methods We retrospectively enrolled pediatric patients younger than 5 years diagnosed with CAP. All 419 S. pneumoniae isolates were tested for antibiotic susceptibility, serotypes, virulence genes, resistance genes, and sequence types. The potential relationships between molecular characteristics were tested by correspondence analysis. Results Most of S. pneumoniae isolates were resistant to erythromycin, tetracycline, clindamycin and trimethoprim-sulfamethoxazole, with 93.8% isolates classified as multidrug resistant. The dominant STs were ST271 (30.8%) and ST320 (12.2%), while the prevailing serotypes were 19F (46.8%), 6B (11.5%), 23F (9.5%) and 19A (9.3%). The coverage rates of PCV-7 and PCV-13 were 73.03% and 86.16%, while the coverage rates of PCV13 among children aged < 1 year and 1-2 years were high in 93.18% and 93.62%. We also observed that CC271 expressed more of mef (A/E), lytA, rlrA and sipA than non-CC271 isolates. Moreover, there were strong corresponding relationships between molecular characteristics. Conclusions The high coverage rate of PCV13 suggests the necessity of introducing the PCV13 vaccine in Western China. Our findings underscore the value of monitoring multiple molecular characteristics to provide new guidance for developing future pneumococcal vaccines.